Growth differentiation factor 15 in patients with congenital dyserythropoietic anaemia (CDA) type II - Casanovas, Guillem; Swinkels, Dorine W.; Altamura, Sandro; Schwarz, Klaus; Laarakkers, Coby M.; Gross, Hans-Juergen; Wiesneth, Markus; Heimpel, Hermann; Muckenthaler, Martina (Journal of molecular medicine, 2011)
Congenital dyserythropoietic anaemias (CDAs) are heterogeneous, hereditary disorders hallmarked by ineffective erythropoiesis and tissue iron overload. Growth differentiation factor 15 (GDF15) was suggested to mediate iron overload in iron-loading anaemias, such as the thalassaemias and CDAI by suppressing hepcidin, the key regulator of iron absorption. Here, we show that serum GDF15 concentrations are elevated in subjects with CDAI and CDAII. Despite similar disease characteristics, CDAI patients present with significantly higher GDF15 concentrations compared to CDAII patients. Hepcidin concentrations are inappropriately low in CDAII patients considering the severe hepatic iron overload associated with this disorder. GDF15 significantly correlates with the degree of anaemia (Hb), the response of erythropoiesis (reticulocyte index) as well as with iron availability in the serum (transferrin saturation). The observation that GDF15 is elevated in CDAII patients is consistent with the proposal that GDF15 is among the erythroid factors down-regulating hepcidin and contributing to iron overload in conditions of dyserythropoiesis.
Gesehen am 28.06.2022